"You Can Connect with Like, the World!": Social Platforms, Survival Support, and Digital Inequalities for People Experiencing Homelessness. Issue 1 (8th November 2021) - Marler, Will
Abstract: This study examines how people experiencing homelessness invest their efforts in locating survival support over social media and crowdfunding and the barriers they experience along the way. Reporting on ethnographic fieldwork with unstably housed adults in Chicago, the study introduces the concept of connective ambition to describe how platform narratives take hold in a context of deep exclusion, informing a view of social media as a vast terrain of untapped support from strangers. Digital inequality emerges in the failure of campaigns to raise money for rent from virtual ties, but also in how limited skills and heightened concerns over privacy and safety discourage most people living on the street from ever seeking out support over social media. Ethnography can help better illustrate the interlocking features of offline and digital inequalities, showing how status-specific uses of social platforms emerge and shape unequal outcomes of digital participation for members of marginalized communities. Lay Summary: Among people experiencing homelessness in Chicago, some attempt to use social media or crowdfunding sites as a way to connect with people online who might offer them support, such as money for rent. This strategy is generally unsuccessful, people who are homeless often lack a social support system and so they turn to online strangers for help rather than people they know offline. Others do not even try to get help over social media, because they are worried about people who wish them harm finding them online, or for their reputations if they admit to being homeless and needing help.